A Comparative Study of Spirituality and Mental Health in spiritual Leaders (Muslim: Gaddi Nasheen, Christian: Fathers) and in adults - Atia Ghafoor; Dr. Um i Lela; Baneeha Zainab (AL-IDRAK JOURNAL, 2023)
The present study was focused on the relationship between spirituality and mental health in spiritual leaders and adult population. It explores the multi-moderation role of spiritual leaders and adult population in term of spirituality and mental health. It was hypothesized that there is likely to be a relationship between spirituality and mental health in spiritual leaders and adult population. There are likely to be gender differences in spirituality and mental. The sample was comprised of (n=174) male and (n=128) female adults. Purposive and snowball sampling technique was used to select participants. For that purpose, the scale The Spirituality in the Workplace: Theory and Measurement by Edwards and Bagozzi (2000), Positive Mental Health (PMH) scale and semi-structured interview was conducted by the participants which used for quantitative data collection spirituality and mental health, qualitative to explore more in depth respectively. Pearson correlation, multi-moderation with help of SPSS and Jesco. Findings of the study showed that there is likely to be a significant negative relationship between spirituality and mental health. Results showed that there is significant positive relationship between spirituality and mental health in spiritual leaders (Gaddi Nasheen, Fathers/sisters) and adult population. Furthermore, more research is needed to better understand the impact of the spirituality on mental health.